HUBUNGAN KEKUATAN OTOT TUNGKAI TERHADAP KETEPATAN SHOOTING KEGAWANG PADA TIM SEPAKBOLA SMPN 6 PEKANBARU - Al Irsyad Jasmi; Saripin '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research ismotivated by the problems is the observation on thefootball team player SMP 6 Pekanbaru still less satisfactory shooting ability toinfluence the goal is one of the leg muscle strength. The purpose of this study was toexamine the relationship leg muscle to determine the accuracy of the shooting on goalin a football SMP Negeri 6 Pekanbaru. This research is an empirical study. Populationand sample in this research is the entire football player SMP 6 Pekanbaru total of 20players. Based on data analysis of data leg muscle strength and precision shootingknown normally distributed. From the calculation, it is known that a high value productmoment correlation (r count) between the legs muscle strength with the precisionshooting at the target in a team SMPN 6 Pekanbaru is 0.605. The calculation result t =3.22 (attached), while t table with df = n-2 = 20-2 = 18 at 95% confidence is 2.10.when t> t Table 3:22> 02:10 with a ring on your PC, so the hypothesis that "there is arelationship leg muscle strength to ensure the accuracy of shooting on goal in a footballSMPN 6 Pekanbaru" acceptable.Keywords: leg muscle strength, accuracy shooting on goal, football